A Mystical Approach in Sīrah Writing (A Study of Madārij al-Nubuwwah) - Dr. Muhammad Humayun Abbas Shams (Journal of Religion and Society, 2025)
The biographers of the Holy Prophet (PBUH) generally present the events of his Sirah in chronological order, followed by a description of his prophetic virtues, excellences, and sublime qualities. Another notable approach is that of the honourable Sufis, who focus on the inner states of the heart and spiritual mysteries. They interpret the Prophet's (PBUH) status, rank, and life events through a metaphysical lens, an approach that may be termed the “spiritual dimensions of Sirah”. Among the prominent prophetic biographers of the subcontinent, Sheikh Abdul Haq Mohaddith Dehlavi stands out for adopting this method in his work Madarij al-Nabuwwah. He draws upon the insights of renowned Sufis such as Shaykh Shihāb al-Dīn, Shaykh Abdul Qādir Jīlānī, and Dāwūd Tā'ī. By following the spiritual and mystical approach, he explains Quranic verses and Ahadith that illuminate the Prophet's (PBUH) excellences. Sheikh Abdul Haq may be regarded as a pioneer who systematically organized and refined this distinctive style in writing the Sirah in the Persian language. This study aims to explore the mystical elements in his biographical writing, highlighting how the Sufi worldview shaped his presentation of the Prophet’s life and virtues. Keywords: Sirah Writing, Mystical Style, Sufi Approach, Madarij al-Nubuwwah, Sheikh Abdul Haq Mohaddith Dehlavi